Optimizing the Role of HIMA PBSI as a Platform for Literary (Poetry) Development through Creative Writing Training and the Utilization of Digital Media - Muhammad Yusron Yusuf; Isnaini Habibatuzzahra; Zumala’in Nuriyasari (CV. Simpati Cloud, 2025)
This study aims to examine and develop the role of the Indonesian Language and Literature Education Student Association (HIMA PBSI) as a platform for literary development, particularly poetry, through creative writing training and the utilization of digital media. The background of this research is grounded in the low level of participation and productivity among PBSI students in producing literary works, despite their academic exposure to literary theory and language skills. This study employs a Research and Development (R&D) method with a descriptive qualitative and quantitative approach. The research subjects consist of students of the Indonesian Language and Literature Education Program who are actively involved in HIMA PBSI. Data were collected through observation, interviews, questionnaires, and documentation. The research procedure included stages of stimulation, problem identification, data collection, data processing, product trials, and conclusion drawing. The findings indicate that poetry creative writing training conducted through workshop-based methods significantly enhances students’ interest, participation, and writing competence. Furthermore, the utilization of digital media has proven effective as a platform for publication and appreciation of students’ literary works. Therefore, HIMA PBSI plays a strategic role in fostering digital literary literacy within the higher education environment.